Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Solve [tex]\(9x + 3y = 15\)[/tex] for [tex]\(y\)[/tex].

A. [tex]\(y = -9x + 5\)[/tex]
B. [tex]\(y = -3x + 5\)[/tex]
C. [tex]\(y = -3x + 15\)[/tex]
D. [tex]\(y = 9x + 15\)[/tex]


Sagot :

We are given the equation [tex]\( 9x + 3y = 15 \)[/tex] and we need to solve for [tex]\( y \)[/tex].

First, we'll isolate [tex]\( y \)[/tex] on one side of the equation.

1. Start with the original equation:
[tex]\[ 9x + 3y = 15 \][/tex]

2. Subtract [tex]\( 9x \)[/tex] from both sides to isolate the terms involving [tex]\( y \)[/tex] on one side:
[tex]\[ 3y = 15 - 9x \][/tex]

3. To solve for [tex]\( y \)[/tex], divide every term by 3:
[tex]\[ y = \frac{15 - 9x}{3} \][/tex]

4. Simplify the right-hand side by dividing both terms in the numerator by 3:
[tex]\[ y = \frac{15}{3} - \frac{9x}{3} \][/tex]

5. This simplifies to:
[tex]\[ y = 5 - 3x \][/tex]

Thus, the solution for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] is [tex]\( y = 5 - 3x \)[/tex].

Comparing this with the provided options:

A. [tex]\( y = -9x + 5 \)[/tex]
B. [tex]\( y = -3x + 5 \)[/tex]
C. [tex]\( y = -3x + 15 \)[/tex]
D. [tex]\( y = 9x + 15 \)[/tex]

The correct answer is:

B. [tex]\( y = -3x + 5 \)[/tex]